New records of Peruvian Reduviidae (Heteroptera) and description of a new species of Tagalis Stål 1860 (Saicinae) - Melo, María Cecilia (2008)
New records of Peruvian Reduviidae are given: Graptocleptes gastricus (Stål) (Harpactorinae); Nitornus lobulatus Stål (Stenopodinae); Nalata armiventris Breddin, Nalata setulosa Stål, Microlestria laevis Champion, and Zelurus umbrifer (Reduviinae); Tagalis inornata inornata Stål, T. seminigra Champion, and the new species Tagalis femorata (Saicinae). General habitus and male genitalia are illustrated, and a key to the species of Tagalis Stål 1860 is presented. The subfamily Saicinae is recorded from Peru for the first time.